Optimalisasi Kegiatan Pengawasan Intern Pemerintah: Evaluasi Penerapan Audit Kinerja - Hesti Setianingsih; Dyah Setyaningrum (Politeknik Ganesha Medan, 2025)
This research aims to evaluate the compliance of the implementation of the performance audit stages by the Government Internal Supervisory Apparatus (APIP), which includes the audit planning, audit execution, and communication of audit results. The method used in this research is a qualitative research approach in the form of a case study with the object of research at the Inspectorate of Ministry X. The Inspectorate of Ministry X is an internal supervisory unit, one of whose duties is to carry out performance audits. The evaluation in this research focused on the performance audit activities carried out by the Inspectorate of Ministry X in 2022. Data collection is conducted through document review and interviews. Data analysis is based on the Guidelines for Performance Audit Implementation in Ministry X, which refers to the Guidelines for Performance Audit Practices published by the Financial and Development Supervisory Agency (BPKP) in 2018. The results of this research show that, overall, the Inspectorate of Ministry X has carried out each stage of the performance audit, starting from the audit planning, audit execution, and communication of audit results, but some activities in those performance audit stages still require improvement in accordance with the Guidelines for Performance Audit Implementation in Ministry X. This is due to the socialization of the guidelines not yet held regularly, the assignment time period is quite short, there is overlapping of assignments, the number and competence of the audit team are not sufficient, and the auditee does not respond to the audit team. This research is expected to contribute to optimizing the implementation of the performance audit in the Inspectorate of Ministry X.